Cryo-EM structure of the botulinum neurotoxin A/SV2B complex and its implications for translocation - Basavraj Khanppnavar; Oneda Leka; Sushant K. Pal; Volodymyr M. Korkhov; Richard A. Kammerer (Nature Communications)
Abstract Botulinum neurotoxin A1 (BoNT/A1) belongs to the most potent toxins and is used as a major therapeutic agent. Neurotoxin conformation is crucial for its translocation to the neuronal cytosol, a key process for intoxication that is only poorly understood. To gain molecular insights into the steps preceding toxin translocation, we determine cryo-EM structures of BoNT/A1 alone and in complex with its receptor synaptic vesicle glycoprotein 2B (SV2B). In solution, BoNT/A1 adopts a unique, semi-closed conformation. The toxin changes its structure into an open state upon receptor binding with the translocation domain (HN) and the catalytic domain (LC) remote from the membrane, suggesting translocation incompatibility. Under acidic pH conditions, where translocation is initiated, receptor-bound BoNT/A1 switches back into a semi-closed conformation. This conformation brings the LC and HN close to the membrane, suggesting that a translocation-competent state of the toxin is required for successful LC transport into the neuronal cytosol.